Incidence of β-lactoglobulin intolerance among lactose intolerance suspected population and diagnostic approach - Dobrevski, Boban; Petreska Ivanovska, Tanja; Zhivikj, Zoran; Sibinovska, Olgica; Efinska Mladenovska, Olivija; Brnjarchevska Blazevska, Teodora; Kirijas, Meri (Macedonian Pharmaceutical Association, Ss. Cyril and Methodius University in Skopje, Faculty of Pharmacy, 2022)
Milk and dairy products have high nutritional value due to its protein, vitamin, mineral and fatty acid content (FAO, 2013). However, regular usage of these products in some individuals may result in manifestation of adverse reactions, such as lactose intolerance (LI) and cow`s milk protein intolerance (CMPI). LI is a syndrome with primarily gastrointestinal symptoms as a result of lactase deficiency in the intestinal mucosa and lactose malabsorption. It can be genetically driven, known as primary LI, where homozygous LCT-13910C and LCT-22018G variants are coding low lactase activity, or secondary LI due to damaged mucosa. CMPI is an immune mediated reaction to milk`s proteins causing abdominal pain, diarrhea, vomitus, nausea etc. Since LI is highly prevalent in the population, while clinical features of LI and CMPI are similar, the last is often misdiagnosed. Treatment of both conditions is mainly based on food restrictions excluding lactose or cow`s milk proteins, so relevant diagnosis is important in successful disease management (Di Constanzo et al., 2019). The aim of this study was to determine the incidence of β-lactoglobulin intolerance (the most frequent form of CMPI) in LI suspected population and to identify diagnostic tools that can help to differentiate CMPI and LI.